Secondary Analyses of the Effects of Lutein/Zeaxanthin on Age-Related Macular Degeneration Progression AREDS2 Report No.3 - Chew, Emily Y. (JAMA Ophthalmol, 2014)
The Age-Related Eye Disease Study (AREDS) formulation for treatment of age-related macular degeneration contains vitamins C, E, beta-carotene and zinc with copper. Age-Related Eye Disease Study 2 (AREDS2) assessed the value of substituting lutein/zeaxanthin in the AREDS formulation because of the demonstrated risk of lung cancer from beta-carotene in smokers and former smokers. As previously reported in a secondary analysis, AREDS2 participants taking lutein/zeaxanthin with or without omega-3 long-chain polyunsaturated fatty 3 acids had a slightly lower progression rate to late AMD than participants not taking lutein/zeaxanthin. OBJECTIVE: To further examine the effect of lutein/zeaxanthin supplementation on progression to late AMD. DESIGN, SETTING, PARTICIPANTS: AREDS2, a multicenter, double-masked randomized trial, of 4203 participants, aged 50 to 85 years, at risk for developing late AMD; 66% had bilateral large drusen and 34% had large drusen and late AMD in one eye. INTERVENTIONS: In addition to taking the original or a variation of the AREDS supplement, participants were randomly assigned in a factorial design to one of the following four groups: placebo, lutein/zeaxanthin (10mg/2mg), omega-3 long-chain polyunsaturated fatty 3 acids (1.0 g), or the combination. MAIN OUTCOME MEASURES: Documented development of late AMD by central, masked grading of annual retinal photographs or by treatment history. RESULTS: In exploratory analysis of lutein/zeaxanthin vs. no lutein/zeaxanthin, the HR the development of late AMD was 0.90 (95% CI: 0.82–0.99), p=0.04. Exploratory analyses of direct comparison of lutein/zeaxanthin vs. beta-carotene showed HRs: 0.82 (95% CI: 0.69–0.96), p=0.02 for development of late AMD, 0.78 (95% CI: 0.64–0.94) p=0.01 for development of neovascular AMD, and 0.94 (95% CI: 0.70–1.26), p=0.67 for development of central geographic atrophy. In analyses restricted to eyes with bilateral large drusen at baseline, the direct comparison of lutein/zeaxanthin vs. beta-carotenes showed HRs: 0.76 (95% CI: 0.61–0.96) p=0.02 for progression to late AMD; 0.65 (95% CI: 0.49–0.85) p=0.002 for neovascular AMD; and 0.98 (95% CI: 0.69–1.39) p=0.91 for central geographic atrophy. CONCLUSION AND RELEVANCE: The totality of evidence on beneficial and adverse effects from AREDS2 and other studies suggests that lutein/zeaxanthin could be more appropriate than beta-carotene in the AREDS type supplements.